Pelatihan Public Speaking untuk Membangun Kepercayaan Diri dan Keterampilan Berbicara pada Ibu-Ibu Pengurus Kelompok Pengajian di Kecamatan Sukorambi Jember - Dahliah Dahliah (Al-Khidmah Jurnal Pengabdian Masyarakat, 2023)
Public speaking skills or public speaking are very useful in the process of self-development for anyone, especially for someone who does have a role in an organization or group in society. However, many people, including women, feel that they are not even able to speak in public because they lack confidence, do not understand the material, or do not understand how to do it. Therefore, public speaking skills must be cultivated, safe and developed continuously. This became the basis for the implementation of the Community Service Program (PKM), which was attended by 25 women representatives from recitation groups in the Sukorambi Jember. The PKM program is packaged in the form of training with the aim of building confidence in public speaking, understanding the material to be delivered, and being able to apply public speaking techniques. During the training, participants receive basic materials and public speaking techniques and the opportunity to practice directly. Implementation starts from the initial observation stage, orientation, introduction of material, practice, and ends with evaluation. The results of the training were quite good, it was proven that at the end of the meeting, the participants had achieved adequate public speaking skills, increased self-confidence, were able to present material well, and were able to apply public speaking techniques.